Investigation of lead bioimmobilization and transformation by Penicillium oxalicum SL2. (September 2018) - Ye, Binhui; Luo, Yating; He, Junyu; Sun, Lijuan; Long, Bibo; Liu, Qinglin; Yuan, Xiaofeng; Dai, Peibin; Shi, Jiyan
Highlights: P. oxalicum SL2 has high ability of Pb bioimmobilization. Secondary minerals were formed during the process of bioimmobilization. Intracellular Pb-complex were detected by TEM-EDS. Pb-oxalate, Pb-citrate, PbHPO4 and Pb-GSH analogues was detected by XANES. Glutathione might play a key role in elimination of the Pb-initialed toxicity. Abstract: Fungi Penicillium oxalicum SL2 was applied for Pb 2+ bioremediation in aqueous solution in this study. After 7 days of incubation at different initial concentrations of Pb 2+ (0, 100, 500 and 2500 mg L −1 ), most of Pb 2+ were removed (90, 98.3, and 86.2%), the maximum Pb content in mycelium reached about 155.6 mg g −1 dw. Meanwhile, the formation of extracellular secondary minerals and intracellular Pb-complex were observed and identified, the speciation of Pb in mycelium was also detected by X-ray absorption near-edge structure (XANES) spectroscopy, i.e., Pb-oxalate, Pb-citrate, Pb-hydrogen phosphate and Pb-glutathione analogues. In addition, content of glutathione and oxidized glutathione was increased under the exposure of Pb 2+, which implied that glutathione might play a key role in Pb immobilization and detoxification in P. oxalicum SL2. This study elucidated partial mechanisms of Pb immobilization and speciation transformation of this strain, providing an alternative biomaterial in the bioremediation of Pb-contaminated wastewater.